Analisis Minat Belajar Siswa Kelas XI Pada Mata Pelajaran Bahasa Inggris Di SMKS Praja Pandawa - Ni Kadek Artini; I Putu Oka Suardana (BADAN PENERBIT STIEPARI PRESS, 2024)
Education plays a key role in human resource development. English, as an international language, holds a crucial role in advancing the quality of education. This article discusses the significance of English language instruction at SMKS Praja Pandawa, a vocational school in Bangli. Despite the focus on tourism, there is a lack of interest in learning English among students. Factors influencing learning interest, such as teaching methods and the learning environment, need to be understood and evaluated by teachers. This research employs a qualitative approach with observation and interview techniques in the 11th-grade class at SMKS Praja Pandawa to analyze students' interest in learning English. The results are expected to provide further insights for enhancing English learning interest in that educational environment.